Optimising design and cost-effective implementation of future pan-African dietary studies: a review of existing economic integration and nutritional indicators for scenario-based profiling and clustering of countries. Issue 1 (15th December 2017) - Aglago, Elom K.; Landais, Edwige; Zotor, Francis; Nicolas, Genevieve; Gunter, Marc J.; Amuna, Paul; Slimani, Nadia
Abstract : Most of the African countries are undergoing a complex nutrition and epidemiologic transition associated with a rapid increase in the prevalence of diverse non-communicable diseases. Despite this alarming situation, the still limited and fragmented resources available in Africa impede the implementation of effective action plans to tackle the current and projected diet–disease burden. In order to address these common needs and challenges, the African Union is increasingly supporting continental approaches and strategies as reflected in the launching of the Agenda 2063 and the African regional nutrition strategy 2015–2025, among others. To assure the successful implementation of pan-African nutritional and health initiatives, cost-effective approaches considering similarities/disparities in economy, regional integration, development and nutritional aspects between countries are needed. In the absence of pre-existing models, we reviewed regional economic integration and nutritional indicators ( n 13) available in international organisations databases or governmental agencies websites, for fifty-two African countries. These indicators were used to map the countries according to common languages (e.g. Arabic, English, French, Portuguese), development status (e.g. human development index), malnutrition status (e.g. obesity) and diet (e.g. staples predominantly based on either cereals or tubers). The review of the indicators showed that there exist similarities between African countries that can be exploited to benefit the continent with cross-national experiences in order to avoid duplication of efforts in the implementation of future pan-African health studies. In addition, including present and future nutrition surveillance programmes in Africa into national statistical systems might be cost-effective and sustainable in the longer term.